2006
DOI: 10.1093/ajcn/83.5.1068
|View full text |Cite
|
Sign up to set email alerts
|

Negative energy balance in male and female rangers: effects of 7 d of sustained exercise and food deprivation

Abstract: Female cadets maintained a significantly more fat-predominant fuel metabolism than did male cadets in response to sustained exercise and semistarvation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 45 publications
(64 reference statements)
6
83
1
Order By: Relevance
“…19 Research on both lean and obese cohorts has demonstrated that RMR reduces rapidly when individuals are placed in energy restriction, with the magnitude of the decrease being greater than can be accounted for by tissue loss. 16,34 RMR of overweight women has been reported to fall by 6% within 10 days of commencing energy restriction (800 kcal per day; B40% WM baseline ), 16 and a comparable (B6%) decrease in resting oxygen consumption was reported after only 4 days of severe energy restriction (450 kcal per day; o25% WM baseline ) in very obese women. 35 In obese women, Bray et al 35 noted that a weight loss of 1 kg every 4 days would be expected based on the baseline-calculated EDef.…”
Section: Discussionmentioning
confidence: 94%
“…19 Research on both lean and obese cohorts has demonstrated that RMR reduces rapidly when individuals are placed in energy restriction, with the magnitude of the decrease being greater than can be accounted for by tissue loss. 16,34 RMR of overweight women has been reported to fall by 6% within 10 days of commencing energy restriction (800 kcal per day; B40% WM baseline ), 16 and a comparable (B6%) decrease in resting oxygen consumption was reported after only 4 days of severe energy restriction (450 kcal per day; o25% WM baseline ) in very obese women. 35 In obese women, Bray et al 35 noted that a weight loss of 1 kg every 4 days would be expected based on the baseline-calculated EDef.…”
Section: Discussionmentioning
confidence: 94%
“…cadets (22 AE 2 MJ/day), but weight-specific TEEs ($350 kJ/kg per day), and physical activity levels (TEE/resting metabolic rate ¼ $3.5) were similar [6 ]. A study of Marine recruits participating in a demanding physically demanding 54 h training exercise also found that men and women performing similar high-intensity activities had similar weight-specific TEEs (men 350 AE 40 kJ/kg per day; women 340 AE 40 kJ/kg per day) [15].…”
Section: Norwegian Ranger Trainingmentioning
confidence: 93%
“…The effects of underfeeding have also been investigated in soldiers participating in military training courses in which study durations are shorter, at 3-62 days, and sleep deprivation and sustained physical activity are added stressors. Study populations range from Norwegian cadets participating in a training course that involves a week of food and sleep deprivation and approximately 23 h/day of marching and other activities [4, 5,6 ], to soldiers participating in 8 weeks of physically demanding US Army Ranger training, in which sleep is restricted to 4 h/day and food is in short supply [7,8]. Others have studied long-range patrols by Swedish ski troops [9], hot weather training by Zimbabwean recruits [10], and a variety of other extremes [11][12][13][14][15] (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Before their eventual rescue they had lost over 20kg each. Although humans can endure several days of heavy physical exercise with limited food rations (Guezennec et al, 1994;Hoyt et al, 2006), by day 95 of the expedition Stroud and Fiennes showed considerable reductions in muscle power, reductions that were linked to marked decreases in cytoplasmic and mitochondrial enzyme activities (Stroud et al, 1997). Two other studies on endurance exercise levels that approach or exceed those of the Arctic explorers, on Tour de France cyclists (Westerterp et al, 1986) and Swedish cross-country skiers (Sjodin et al, 1994), respectively, show somewhat smaller deficits, or even complete energy balance.…”
Section: Introductionmentioning
confidence: 99%